Efektivitas Integrasi Pupuk Bokashi Kotoran Kambing dan Pupuk Organik Cair (POC) Kulit Pisang terhadap Pertumbuhan dan Produksi Tomat (Lycopersicum esculentum L.) - Anisa, Anisa; Renfiyeni, Renfiyeni; Yora, Muharama (Eduscience Development Journal, 2026)
Tomato (Lycopersicum esculentum L.) is a horticultural crop of considerable economic importance, valued for its nutritional and functional properties. Despite its potential, enhancing tomato productivity remains a critical challenge. This study aims to evaluate the effectiveness of integrated fertilizer application and to determine the optimal dosage of the combination of goat manure bokashi and banana peel–based liquid organic fertilizer (POC) on the vegetative growth and fruit yield of tomato plants. The experiment was conducted from April to July 2024 in Supayang Village, Payung Sekaki District, Solok Regency, West Sumatra Province, situated at an elevation of 700 meters above sea level. A Randomized Block Design (RBD) was employed, comprising six treatment groups and four replications. The treatments included: PO (control), P1 (bokashi 20 tons/ha + POC 120 ml/L), P2 (bokashi 20 tons/ha + POC 170 ml/L), P3 (bokashi 20 tons/ha + POC 220 ml/L), P4 (bokashi 20 tons/ha), and PS (POC 220 ml/L). Statistical analysis revealed that the integrated application of goat manure bokashi and banana peel POC significantly influenced plant height, stem diameter, days to 50% flowering, harvest time, and fruit count per plant. However, no statistically significant effect was observed on fruit weight per plant across the treatments.